Transformation in Content of Bioactive Compounds of Glodok Fish (Boleopthalmus boddarti) Based on the Effect of Variations in Temperature and Frying Time - Ridho, Moh. R.; Patriono, Enggar; Cahyani, Ajeng; Avesena, Muhammad; Fitria, Syarifa (Current Bioactive Compounds, 2023)
Background: Glodok fish (Boleophthalmus boddarti) was identified to contain bioactive compounds such as steroids, terpenoids, bufadienolid, carotatoksin, and corticosteroids. These compounds benefit human life, and Lampung coastal communities consume the fish to cure asthma. Various processing methods, such as frying, are used to prepare the fish. The frying process can damage vitamins, proteins, and bioactive compounds. However, there is no data regarding the effect of using different temperatures and times on changes in the bioactive content of the fish. Methods: Sampling was conducted around the mouth of Musi River, South Sumatra. The stages consisted of the preparation process and treatment using 9 variations of temperature and frying time, sample extraction, and bioactive compounds' content analysis by GC-MS. Results: The results showed that the bioactive compounds consisted of corticosteroids, steroids, carotenoids, monoterpenoids, sesquiterpenoids, and triterpenoids. Conclusion: Variations in the treatment resulted in cholesterol of the steroid group in the highest treatment at 14.36% and the loss of betamethasone acetate compounds in the corticosteroid by 0.07%.
Keywords: frying